N-3 polyunsaturated fatty acids in heart failure: mechanisms and recent clinical evidence - Marchioli, R.; Silletta, M. G.; Levantesi, G.; Pioggiarella, R.; Tognoni, G. (Cellular and Molecular Biology, 2010)
Over the past 20 years, there has been significant progress in our knowledge of the pathophysiology of heart failure (HF) with consequent considerable development of both pharmacological and non pharmacological approaches. Despite improved therapeutic strategies, HF still remains burdensome in terms of mortality, quality of life, and hospitalization costs. A new and promising medical treatment to improve survival in HF patients stems from the recent results of the Italian study, Gruppo Italiano per lo Studio della Sopravvivenza nell'Infarto Miocardico-Heart Failure (GISSI-HF). GISSI-HF was a randomized, large scale, double-blind, placebo-controlled trial showing that n-3 PUFA (850–882 mg/d) reduced mortality and admission to the hospital for cardiovascular reasons in patients with chronic heart failure (HF) who were already receiving recommended therapies. The clinical benefit observed in GISSI-HF seemed to be mediated prominently by the antiarrhythmic effects of n-3 PUFA, though an effect on mechanisms related to HF progression cannot be excluded. This article presents the results of GISSI-HF study and reviews the previous clinical evidence on n-3 PUFA and risk of heart failure and discusses in depth the potential mechanisms through which n-3 PUFA treatment can improve clinical outcome in HF patients.